Advancing Sustainability Through Holistic Ministry of Local Churches in North Sulawesi - Vanny Suoth; Riedel Gosal; Matulandi Tewu; Putri Tengor; Sion Ering; Joni Kutu' Kampilong; Valdo Woruntu (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines why local churches in North Sulawesi, Indonesia, struggle to translate their theological commitments to justice and creation care into sustained and holistic ministries aligned with sustainability principles. Using a sequential explanatory mixed-methods design, data were gathered from 178 congregants, four focus groups (n=32), and eight key informant interviews across three Protestant churches. The study identifies five issues interrelated like: (1) the gap in the operation; (2) the human resources gap; (3) the financial weakness; (4) the cultural-theological gap; and (5) the underutilized assets.. Critically, these barriers reinforce themselves, creating a self-perpetuating cycle of inertia. The study provides an empirically grounded understanding of faith-based sustainability challenges in the Global South, shifting the discourse from deficit-based to asset-based approaches. It highlights the importance of holistic interventions that simultaneously focus on theological re-education, institutional capacity, and financial innovation. Strategies such as designing stepwise ministry toolkits, establishing minor lay-coordinating roles, creating various funding sources through social enterprises or grants, and redefining ecological and social action as part of the ecclesial identity are among the recommendations. Such findings provide a replicable template for churches worldwide that seek to connect faith and sustainable action in ways that resonate with their cultures